2013
DOI: 10.1163/15718182-02102006
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Rights Research Moving into the Future – Challenges on the Way Forward

Abstract: The expansion of the research into children’s rights during the last 20 years has constituted children’s rights research as an established and legitimate field of study. The time may now be ripe to reflect on the work undertaken so far and to consider the future of children’s rights research. In recent years, self-critical voices have surfaced within the research field, pointing out possible areas of concern. The ambition of this paper is to contribute to such deliberations within children’s rights research. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 27 publications
0
74
0
12
Order By: Relevance
“…Reflecting critically involves recognising the historic political process of writing the CRC as giving rise to a limited set of rights that are not set in stone, and enabling exploration of the norms and logics of the CRC with reference to political and philosophical theory, rather than relying on frameworks like the 'Three Ps' (Protection, Provision and Participation) which have little theoretical basis (Quennerstedt, 2013). Not engaging in such critique within research would be in tension with some 'new' sociology of childhood approaches which question the conceptions of childhood within the CRC (Alanen 2011).…”
Section: Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Reflecting critically involves recognising the historic political process of writing the CRC as giving rise to a limited set of rights that are not set in stone, and enabling exploration of the norms and logics of the CRC with reference to political and philosophical theory, rather than relying on frameworks like the 'Three Ps' (Protection, Provision and Participation) which have little theoretical basis (Quennerstedt, 2013). Not engaging in such critique within research would be in tension with some 'new' sociology of childhood approaches which question the conceptions of childhood within the CRC (Alanen 2011).…”
Section: Contextmentioning
confidence: 99%
“…A third element of critical children's rights research framed from below might, then, go beyond the goal of enabling children to define their rights, to also support their protagonism. Although linking to a universal level is secondary (Quennerstedt 2013), combining contextualised rights with universal human rights principles remains a necessary challenge if a rights-based 6 approach is to be used as a robust advocacy tool (Tobin 2011). Recognising universal rights conveys respect and creates conditions which foster rights holders' agency and provide a resource for building reasoned arguments (Freeman 2011).…”
Section: Children As Rights-holders To Claim Their Rights and Buildmentioning
confidence: 99%
See 2 more Smart Citations
“…Children's rights research has since developed into a relatively well-established field of study, as demonstrated by the rising number of publications, research activities and researchers involved (Quennerstedt, 2013). Dominant research interests were concerned with the instrumental dimension of children's rights such as advancing the implementation of the UNCRC on the local, national, regional and global political levels.…”
mentioning
confidence: 99%